Effect Size for Token Economy Use in Contemporary Classroom Settings: A Meta-Analysis of Single-Case Research. Issue 4 (1st December 2016) - Soares, Denise A.; Harrison, Judith R.; Vannest, Kimberly J.; McClelland, Susan S.
Abstract: Recent meta-analyses of the effectiveness of token economies (TEs) report insufficient quality in the research or mixed effects in the results. This study examines the contemporary (post-Public Law 94-142) peer-reviewed published single-case research evaluating the effectiveness of TEs. The results are stratified across quality of demonstrated functional relationship using a nonparametric effect size (ES) that controls for undesirable baseline trends in the analysis. In addition, moderators (i.e., classroom setting, age of participant, outcomes, use of response cost, and use of verbal cueing) were analyzed. Eighty-eight AB phase contrasts were calculated from 28 studies (1980–2014) representing 90 participants and produced a weighted mean ES of 0.82 ( SE = 0.03, 95% CI [0.77, 0.88]). Strong quality produced a combined weighted mean ES of 0.85 ( SE = 0.642, 95% CI [0.74, 0.97]). Moderator analyses revealed that a TE was slightly more effective for youth between the ages of 6 and 15 years than for children between the ages of 3 and 5 years or when used with behavioral goals in comparison to academic goals. However, no difference was found when implemented in general or special education settings or with the inclusion of response cost or verbal cueing.